Study on Design Method of Pile Wall Combination Structure in a Deep Foundation Pit Considering Deformation Induced by Excavation - Wu, Changjiang; Yu, Jun; Cao, Xiaojian; Shen, Wuqin (Frontiers in Earth Science, 2022)
The technology of pile wall combination in deep foundation pit takes advantage of the large stiffness of retaining pile together with basement wall to resist soil and water pressure. As a part of basement wall, the existence of retaining pile can reduce the thickness of basement wall. However, the current design theory of pile wall combination in deep foundation pit doesn’t consider the influence of deformation induced by excavation and the interaction mechanism between the retaining pile and basement wall. Therefore, a composite structure model of elastic subgrade beam associated with continuous beam is proposed, and elastic spring is introduced to simulate the interaction between pile and basement wall. The finite difference equation and calculation method are established to figure out the internal force and displacement of pile wall combination structure. Compared to the results of field monitoring and FEM by the commercial software, this analytical method is proved to be able to accurately study the internal force and deformation of retaining pile during the excavation stage. Based on the above results, further investigation is carried on the interaction between pile and basement wall during the construction and normal service stage of basement structure. It is concluded that the existence of basement wall can reduce the lateral displacement on the top of retaining pile caused by removal of strut and affect the bending moment of upper part of retaining pile among the depth of basement wall, with almost no influence on the part below the bottom of pit. The bending moment of basement wall is closely related to the deformation of retaining pile and changes with the working condition. In addition, further factor sensitivity analysis shows that pile-wall relative stiffness ratio and stiffness of horizontal beam and slab of basement make significant influence on the interaction between pile and basement wall.